A preliminary study on internal filtration mechanism by using nonwoven filter medium - Kadooka, Hiroto; Manabe, Masaki; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2016)
When a nonwoven filter medium is used as a prefilter or as a cyclic filter for liquid filtration, filter life is sometimes given priority over particle rejection performance. Such filter medium has been selected so far by trial and error, since the filter life depends on many factors such as filter medium structure, characteristics of particles to be removed, and operational conditions of the filtration process. In order to elucidate the effects of these factors on the filter life, fundamental study using filter paper as a model nonwoven filter medium and monodispersed spherical PMMA particles as a model suspended material has been conducted under constant rate filtration conditions. The changes in pressure drop p across the filter unit and turbidity of the filtrate with respect to filtrate volume v have been observed. The clarity of the filtrate decreased at the initial stage of filtration, then increased in every subsequent experimental run; dp/dv as a measure of the increment of filtration resistance also decreased at the initial stage of filtration, then increased approaching a plateau value. These results imply the existence of a filtration mechanism, where filtration efficiency decreases with time, earlier than what could be predicted by conventional blocking filtration and cake filtration models. Overall filtration resistance mainly depends on the cumulative mass of captured particles, and is slightly affected by both feed solid concentration and filtration rate.